Plasma Astrophysics, Part II Reconnection and Flares - Somov, Boris V. (Astrophysics and Space Science Library,, 2013)
This two-part book is devoted to classic fundamentals and current practices and perspectives of modern plasma astrophysics. This second part discusses the physics of magnetic reconnection and flares of electromagnetic origin in space plasmas in the solar system, single and double stars, relativistic objects, accretion disks and their coronae. More than 25% of the text is updated from the first edition, including the additions of new figures, equations and entire sections on topics such as topological triggers for solar flares and the magnetospheric physics problem. This book is aimed at professional researchers in astrophysics, but it will also be useful to graduate students in space sciences, geophysics, applied physics and mathematics, especially those seeking a unified view of plasma physics and fluid mechanics.